2020
DOI: 10.3389/fmed.2019.00338
|View full text |Cite
|
Sign up to set email alerts
|

Comparable Long-Term Outcomes of Cyclosporine and Infliximab in Patients With Steroid-Refractory Acute Severe Ulcerative Colitis: A Meta-Analysis

Abstract: Background: In steroid-refractory acute severe ulcerative colitis (ASUC), cyclosporine (CYS) or infliximab (IFX) may be considered as a second-line alternative to avoid colectomy. There are short-term data reported, but until now, there is no meta-analysis regarding long-term outcomes of CYS and IFX in patients with ASUC. Aim: To compare long-term efficacy and safety of CYS and IFX in a meta-analysis. Methods: Three electronic databases (PubMed, Embase, Cochrane Central Register of Controlled Trials) were sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 55 publications
(102 reference statements)
1
6
0
1
Order By: Relevance
“…37 Both the aforementioned meta-analyses found that there were no significant differences between infliximab and ciclosporin in terms of drug-related adverse events, serious adverse events, or mortality. 14,33 Our results also demonstrated no significant differences between the two drugs in terms of serious adverse events.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…37 Both the aforementioned meta-analyses found that there were no significant differences between infliximab and ciclosporin in terms of drug-related adverse events, serious adverse events, or mortality. 14,33 Our results also demonstrated no significant differences between the two drugs in terms of serious adverse events.…”
Section: Discussionsupporting
confidence: 53%
“…Another meta-analysis evaluating long-term outcomes of ciclosporin and infliximab in patients with acute severe UC in observational studies and RCTs reported a significantly higher colectomy-free survival rate with infliximab compared with ciclosporin. 33 This difference was only seen within the first 3 years after rescue therapy and was found in observational studies of infliximab but, importantly, not in RCTs.…”
Section: Discussionmentioning
confidence: 98%
“…Notably, there are dozens of ways to perform meta-analyses of different studies, and RRA is only one of them. We reviewed the current studies on ulcerative colitis (Bopanna et al, 2017;Gubatan et al, 2019;Szemes et al, 2019;Chen M. et al, 2020;Li et al, 2020;Sankarasubramanian et al, 2020;Yoon et al, 2020;de Carvalho et al, 2021;Ye et al, 2021). We believe that the advantage of RRA analysis is that more potential biomarkers can be found at one time, which can provide clues for subsequent research.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, treatment failure was seen in 60% (OR 1.4) of those treated with CyA compared to 54% (OR 1.3) of those treated with IFX, with no significant difference in colectomy or serious adverse event rates [39]. In a very recent meta-analysis comparing long-term outcomes with CyA and IFX in patients with steroid-refractory ASUC, pooled odds ratio for colectomy-free survival was higher with IFX compared to CyA at 1-, 2-, and 3-year follow-up [40]. However, at the fourth year, this difference was no longer detectible.…”
Section: Infliximab and Cyclosporinementioning
confidence: 98%